Occurrence and risk assessment of endocrine-disrupting chemicals in wastewater treatment plants in the Chaohu Lake Basin - Han, Yalin; Qi, Cuicui; Niu, Ziniu; Li, Nini; Tang, Jie (Frontiers in Environmental Science, 2024)
The effluent and residual sludge from wastewater treatment plants (WWTPs) frequently contain endocrine-disrupting chemicals (EDCs). These chemicals are difficult to detect and break down, and have the potential to accumulate in the environment, presenting risks to ecosystems and human health. In this study, the Tangxi River (TXH), Zipeng Mountain (ZPS), Lianxi (LX), and Wang Xiaoying (WXY) WWTPs were used as the study objects, and the environmental exposure indexes of EDCs in their effluent and sludge were investigated in the spring, summer, autumn, and winter from October 2017 to October 2018. The pollutants with 100% detection rates in the effluent of the four WWTPs were 4-n-nonylphenol (NP) and di-2-ethylhexyl phthalate (DEHP), while only DEHP had a 100% detection rate in the sludge. Different pollutants had clearly different seasonal and spatial characteristics,and their removal rates also vary significantly. Bisphenol A (BPA) was detected in the TXH effluent with a maximum value in autumn, which was significantly higher than in other seasons and for other WWTPs. Benzo(a)pyrene (B(a)P) was only detected in the sludge in spring and summer and only in TXH and WXY effluent. Through positive matrix factorization (PMF) source analysis under influent data it was assessed that the main source of pollutants was industrial wastewater discharge. An ecological risk assessment revealed that the risk quotient (RQ) of estriol (E3) in the effluent of the TXH was a high risk in autumn, DEHP may pose a carcinogenic risk through drinking water pathway.